2013
DOI: 10.1097/ta.0b013e3182984911
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability after burn injury

Abstract: Epidemiologic/prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 25 publications
1
50
0
1
Order By: Relevance
“…Recently, in burn patients, we reported a reduced R time in those who developed DVT. 19 In all these previous studies, including our own, the difference in TEG was ''statistically'' significant, but it might be difficult to make clinical decisions based on an R or MA values that are only slightly outside the normal range.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Recently, in burn patients, we reported a reduced R time in those who developed DVT. 19 In all these previous studies, including our own, the difference in TEG was ''statistically'' significant, but it might be difficult to make clinical decisions based on an R or MA values that are only slightly outside the normal range.…”
Section: Discussionmentioning
confidence: 95%
“…There is no routine laboratory test for hypercoagulability, and shortened PT or PTT have little relevance. Various studies identify differences in TEG R time, 19,26 MA, 17 and platelet numbers or function. 28 In this present study, hypercoagulability was defined as one or more TEG variables outside the standard reference range.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Albeit those studies have been conducted in populations with a high incidence of in-house thromboembolism, such as trauma patients, current evidence supporting an association between TEG and clinical VTE is scarce [14][15][16][17]. When used as a predictor of DVT or pulmonary embolism, TEG has shown considerable variability in sensitivity and specificity among studies.…”
Section: Introductionmentioning
confidence: 96%
“…[23, 29, 30] It has been previously shown that thermally injured patients become hyper-coagulable within one week of burn injury, despite a normal coagulation profile on admission. [31] In regards to the PICC line itself, PICC associated UEDVT typically occurs day 7–14 after line insertion. [7, 9] This was in fact observed in our patient population, where UEDVT occurred on post-insertion day 7, 9, and 9 respectively, despite all receiving chemical thrombo-prophylaxis (Table 4).…”
Section: Discussionmentioning
confidence: 99%